The economic consequences of health shocks - McKee, Sophie, author; Zahran, Sammy, advisor; Mushinski, David, advisor; Pena, Anita, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2018)
This dissertation is composed of three chapters which examine the extent of reverse causation or the causal pathway in going from health to financial components of social economics status (SES) on the heath-SES gradient in Western Europe. In Chapter 1, I construct two population health metrics for survey-based data suitable for analysis across time and populations. To do so, I combine objective health indicators with the information available in the Survey of Health, Ageing, and Retirement in Europe (SHARE) dataset regarding health functioning and prognosis, and develop a strategy to assess and quantify a multidimensional concept of health that minimizes the influence of subjective factors (country, wave, age, and labor status) in the assessment process. The first variable, Health Stock, is an objective comprehensive health metric, which is a composite of an individual's level of function at a point in time as well as their expected transition to other levels of health in the future. The second variable - referred to as Functioning Stock – is restricted to the objective measures of an individual's level of function. In Chapter 2, I investigate the short term impacts of negative health shocks on the labor outcomes of working individuals across levels of education and country of residence in Western Europe. I propose a new definition of negative health shock as the onset of a decrease between two consecutive periods in the Functioning Stock, whose magnitude exceeds a given threshold (in percentage terms). The analysis identifies three countries (Switzerland, Sweden, and Spain) that are best at mitigating the occurrence of negative health shocks, other things held equal. I then show that on average in the European countries examined, labor outcomes are dose-responsive with the intensity of the health shock, and that the impact of a health shock is "U-shaped" across levels of education: compared to workers with a medium or high levels of education, the probability of having work as the only source of personal income ("working only") for low-skilled workers and for college-educated workers is less affected by the occurrence of a health shock. Assuming the loss of earned income is not fully compensated by benefits, we could infer that in the short term, reverse causation for negative health shocks could be steepening the slope of the SES-Wealth gradient for workers with the middle range level of education. I then investigate the cross-country variation in the magnitude of the impact of a health shock on the probability to continue "working only". First, we find that the rates of people left without labor income or benefits are extremely low in every country considered, indicating that social safety nets are effective. Without delving into the complexities of the country-specific social insurance systems and the associated variation in benefit generosity, it is impossible to conclude on the relative magnitude of reverse causation across countries. However, two groups of countries stand out by the way workers maintain a connection to employment following a decline in health. In Switzerland, where health impaired workers have the highest probability to continue working, the short term impact of reverse causation is smallest. A hybrid labor force status is prevalent in Sweden, Spain, Belgium, and to a lesser extent in France and Denmark, where a substantial fraction of health impaired workers start receiving benefits but do not sever ties completely with work. In Chapter 3, I investigate the determinants of the probability of working in the second period for middle-age male individuals in Western Europe, examining in particular the weight of their work force status in the first period. I show that the impact of the initial work force status is magnified in the case of an improvement in health: individuals whose mental or physical capacities improve and who were working while receiving benefits are about 25% more likely to have work as their only source of income in the following two-year period than comparable individuals whose health did not improve. By contrast, these numbers hover around zero for males who had severed all ties with work, confirming the existence of a benefit trap. Flexible benefit schemes that enable work and the receipt of benefits appear to perform the dual function of catch and release: such schemes cushion individuals from the impact of a decline in health with the receipt of benefits while maintaining an attachment work, allowing closer alignment of the individual’s work trajectory with their preferences and capacities. As European populations age and become more frail, results from this dissertation suggest that the impact of reverse causation should steepen the health-wealth gradient, particularly for individuals with secondary school education. To limit this effect, public policies should (1) mitigate the occurrence of health shocks in the first place, (2) support individuals who wish to continue working as long as they are physically and mentally able, and (3) offer hybrid solutions that incentivize work together with the receipt of benefits to health impaired individuals. Other European countries could draw on the experiences of Switzerland and Sweden, who have proven to be most successful at implementing such policies.
Keywords: health shocks; labor supply; health-wealth gradient; benefit trap